Diabetes modifies the association of prehypertension with cardiovascular disease and all‐cause mortality. Issue 6 (4th April 2021) - Ren, Yanlong; Zuo, Yingting; Wang, Anxin; Chen, Shuohua; Tian, Xue; Li, Haibin; He, Yan; Wu, Shouling; Ma, Changsheng
Abstract: Prehypertension is a risk factor for cardiovascular disease (CVD) and all‐cause mortality. However, it is unclear whether prehypertension combined with diabetes associate with a higher risk for cardiovascular disease and all‐cause mortality. The purpose of this study was to explore the relationship between prehypertension and the risk of CVD and all‐cause mortality was different among individuals with or without diabetes. In the prospective community‐based Kailuan study, 67 344 participants without hypertension or a history of CVD at baseline (2006) were included. Prehypertension was defined as systolic blood pressure of 120–139 mmHg or diastolic blood pressure of 80–89 mmHg. The outcomes were CVD and all‐cause mortality were followed up through December 31, 2017. We performed Cox proportional hazards models to evaluate the relationships between prehypertension and CVD and all‐cause mortality by diabetes status. During a median follow‐up of 11.03 years, 2981 CVD events and 4655 all‐cause mortality occurred. After adjusting age, sex, and other factors, the associations of prehypertension with risk of CVD and all‐cause mortality were significant in participants without diabetes (hazard ratio and 95% confidence interval: 1.54 [1.38–1.71] and 1.27 [1.17–1.38]), but not in participants with diabetes (1.20 [0.93–1.56] and 0.88 [0.73–1.07]). The interactions between prehypertension and diabetes for the risk of CVD and all‐cause mortality were all significant (all p  < .05). Prehypertension was only associated with an increased risk for CVD and all‐cause mortality in non‐diabetes participants. Diabetes modifies the relation of prehypertension with the risk of CVD and all‐cause mortality.